Verspätungen und Störungen an intermodalen Verkehrsknoten besser managen; Coordinated delay management at intermodal transport hubs - Janina D. Scheelhaase; Benedikt Scheier; Erik Grunewald; Saskia Seidel; Thomas Christ; Ulf Noyer; Sven Maertens; Gunnar Knitschky; Florian Rudolph (Wirtschaftsdienst, 2022)
Der Beitrag zeigt anhand einer typischen Verspätungssituation an einem intermodalen Verkehrsknoten die verkehrlichen und ökonomischen Effekte dieser Verspätung für verschiedene Stakeholder auf (Störfallszenario). Weiterhin wird ein Szenario zur Verbesserung der Verspätungssituation, in dem die einzelnen Stakeholder am Verkehrsknoten auch intermodal kooperieren (Kooperationsszenario), entworfen und in seinen Effekten mit dem Störfallszenario verglichen. Der Vergleich der verkehrlichen und ökonomischen Effekte beider Szenarien ermöglicht Aussagen über die relative Vorteilhaftigkeit eines kooperativen Verspätungs- und Störfallmanagements an intermodalen Verkehrsknoten. – – Delays due to missed connections at an intermodal hub such as an airport or train station may cause individual and overall economic costs. Travelers experience individual stress and may incur costs due to missed business appointments or lost vacation or spare time, for example. Transportation companies may encounter higher costs due to a delay, e.g., for additional employees or overtime, including at night, as well as for rebooking, compensation payments on the basis of passenger rights regulations, or, for example, if entire journeys or flights have to be canceled due to delays. Currently, delays are hardly considered and managed in a coordinated way as expert interviews conducted by the authors revealed. Our modelling results indicate that a coordinated intermodal delay management at intermodal hubs that considers the whole travel chain on the way to the airport can lead to advantages over the current, uncoordinated management of delays.
Keywords: R41; L92; L93; 330; Verkehr; Verkehrsfluss; Linienverkehr; Verkehr; Verkehrsfluss; Linienverkehr